CHATBOT FOR EDUCATIONAL SERVICES:CONFIRMATION AND ASSESSMENT OF QUALITY DIMENSIONS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The increased use of digital devices and  integration of information technology has  resulted in a rise in the development and  implementation of artificial intelligence-based  bots. Education sector is no exception and is  actively exploiting the capabilities of chatbots  for teaching and learning. Delhi University too  took a leap forward in this regard by enabling  its admission chatbot in the current academic  session. Since research in this domain is still in  its infancy, the present study was undertaken to  provide an understanding of the chatbot quality  and effectiveness for academic institutions.  Responses obtained from 226 students who had  used the admission chatbot were analyzed using  the technique of CFA and SEM. The results  confirm 13 dimensions of chatbot quality for  educational services. Further, the performance  of the admission chatbot is found to be above  average for all the dimensions, indicating the  scope as well as need for improvement in its  quality and effectiveness, especially with respect  to the dimensions of Personalization, Security,  and Information Quality which have been  revealed to be exerting a significant impact on  the overall experience of the users (i.e., students).  The findings thus help in identifying important  constituents of chatbot quality and may be used  by higher education institutions and Universities  to develop and integrate chatbots in teaching  and learning activities to yield desired experience  for students across different disciplines and  courses.
Keywords: Chatbot; Quality Dimensions; User Experience; Educational Services